2002
DOI: 10.1034/j.1600-051x.2002.290906.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of aggressive periodontitis in school attendees in Uganda

Abstract: A relatively high prevalence of EOP (28.8%) was found in young Ugandan school attendees, with 6.5% of these showing severe disease. EOP in Uganda was significantly more prevalent in males than females, and most frequently characterized by approximal involvement of molars and mandibular incisors. Etiologic and predisposing factors associated with the high occurrence of EOP in Uganda, as well as therapeutic and preventive measures of the disease in this population, remain to be delineated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
74
3
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 25 publications
(40 reference statements)
13
74
3
7
Order By: Relevance
“…In the present study, AP was not specified in its localized and generalized forms. This can result in a possible inclusion of what has been defined as the "incidental disease" [9] [10]. However, Open Journal of Stomatology the recent result was approximately similar to those found in Brazil in subjects aged between 12 and 29 years old [18].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In the present study, AP was not specified in its localized and generalized forms. This can result in a possible inclusion of what has been defined as the "incidental disease" [9] [10]. However, Open Journal of Stomatology the recent result was approximately similar to those found in Brazil in subjects aged between 12 and 29 years old [18].…”
Section: Discussionmentioning
confidence: 60%
“…But a study by Albandar et al [9] in Uganda among 12 -25 years old of the patients found a high prevalence of 28.8% of early-onset periodontitis. Thus, the prevalence in Africa appears therefore to be high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mwokorie and Arowojolu found a prevalence of 1.6% in a population group whose age ranged from 17 to 34 in a Nigerian hospital (25) . Albandar et al reported high prevalence levels of aggressive periodontitis among Ugandan students aged 12-25; of which 6.5% showed generalized or localized aggressive periodontitis; and 22% showed incidental aggressive lesions (26) . Hodge et al suggested that genetic factors are more significant than history of smoking in the manifestation of generalized aggressive periodontitis (27) .…”
Section: Epidemiologymentioning
confidence: 99%